2022
DOI: 10.3390/cancers14010229
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of LAT1-4F2hc in Urological Cancers via Toll-like Receptor and Other Vital Pathways

Abstract: Tumor cells are known for their ability to proliferate. Nutrients are essential for rapidly growing tumor cells. In particular, essential amino acids are essential for tumor cell growth. Tumor cell growth nutrition requires the regulation of membrane transport proteins. Nutritional processes require amino acid uptake across the cell membrane. Leucine, one of the essential amino acids, has recently been found to be closely associated with cancer, which activate mTOR signaling pathway. The transport of leucine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 119 publications
0
7
0
Order By: Relevance
“…In recent years, LAT1 has emerged as a viable drug target for multiple diseases and disorders such as cancer and autism spectrum disorder (ASD). , Currently, most of the drug discovery efforts targeting LAT1 have focused on inhibitors targeting the substrate-binding site. For example, there are two orthosteric substrate-binding site inhibitors of LAT1 that are currently under clinical investigation for treating patients with advanced biliary tract cancers (JPH-203) and advanced pancreatic cancer (OKY 034) .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, LAT1 has emerged as a viable drug target for multiple diseases and disorders such as cancer and autism spectrum disorder (ASD). , Currently, most of the drug discovery efforts targeting LAT1 have focused on inhibitors targeting the substrate-binding site. For example, there are two orthosteric substrate-binding site inhibitors of LAT1 that are currently under clinical investigation for treating patients with advanced biliary tract cancers (JPH-203) and advanced pancreatic cancer (OKY 034) .…”
Section: Discussionmentioning
confidence: 99%
“…It was verified that EVs promote angiogenesis, support the growth and expansion of tumors, and transmit anticancer drugs outside the BC cells, leading to drug resistance [ 34 ]. Moreover, tumors grow and evolve through a constant crosstalk with the surrounding microenvironment, and emerging evidence indicates that angiogenesis and immunosuppression frequently occur simultaneously in response to this crosstalk [ 35 ]. Accordingly, strategies combining antiangiogenic therapy and immunotherapy seem to have the potential to tip the balance of the tumor microenvironment and improve treatment response [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…LAT1 (SLC7A5) was discovered in 1998 [ 3 , 9 ]. It combines with 4F2hc (SLC3A2) heavy chain protein to form a transmembrane complex to play its biological role [ 10 ]. LAT1 is mainly responsible for the transport of large neutral amino acids.…”
Section: The Structure and Function Of Latsmentioning
confidence: 99%
“…There is no clear research result on the role of LAT1 in T cell differentiation, but previous studies have shown that LAT1 is related to the metabolic process of T lymphocyte differentiation. LAT1 expression is low in intrinsic T cells, whereas T cells at the differentiation stage specifically increase LAT1 expression by T cell receptors (TCR), ensuring sufficient nutrients to react with the antigen [ 10 , 14 ].…”
Section: The Structure and Function Of Latsmentioning
confidence: 99%
See 1 more Smart Citation